Accessibility to social interest housing for wheelchair user: a case study - Santos, Aguinaldo dos (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper presents a set of guidelines developed to help architects, engineers, designers on the design of accessible houses for low income people, with emphasis on people using wheelchair. Case study as the main research strategy and the scope of the project was limited to the buildings plans. A literature review enabled the development of a theoretical framework that was used on the analysis of the case study. The case study allowed a critical analysis on the minimum areas per room pointed out in the literature as suitable for low-income houses against acceptable patterns for people on wheelchair. The study proposes an alternative strategy for implementing accessibility involving two stages: minimum and advanced. The case study results have shown that the minimum level already increases the construction costs in 30%. However, the improvement in the quality of life of the disable person is improved drastically and it allows a reduction and even elimination of those resources that would be required for adapting the house throughout its life cycle.